Comparative simulation research on the stress characteristics of supercritical carbon dioxide jets, nitrogen jets and water jets. Issue 1 (1st January 2017) - Li, Mukun; Ni, Hongjian; Wang, Ruihe; Xiao, Caiyun
ABSTRACT: In previous studies it has been shown that supercritical carbon dioxide (SC-CO2 ) jets are more efficient at rock breaking than water jets, but the corresponding systematic mechanism explanations were not available. Therefore, this paper conducts an in-depth analysis of the fluid properties with equations suggested by the American National Institute of Standards and Technology (NIST), establishes the fluid-solid-heat coupling model with the support of ANSYS, and reveals the stress responding mechanism of SC-CO2, water and nitrogen jets. When the rock is at room temperature, the jets increase the temperature of the rock and generate thermal stress. Furthermore, the temperature elevation effect decreases in the sequence of water at 70°C, nitrogen at 70°C, carbon dioxide at 70°C and water at 27°C. In comparison with water jets at 27°C, jets at 70°C in carbon dioxide increase the maximum stress range and the high stress range of rock, accounting for the low threshold pressure and large volumes of rock breaking in the current literature. For jets at the same temperature (70°C), the stress in rock decreases in the sequence of water, nitrogen and carbon dioxide, indicating that previous studies have not taken the effects of the temperature into consideration, leading to the incorrect conclusion that carbon dioxide is more efficient for rock breaking. In addition, this paper also analyzes the jet field and the stress field with respect to the formation temperature and finds a decrease in thermal stress generated by jets produced at rock temperature. Both the temperature decreasing effect and the rock breaking stress decrease in the sequence of carbon dioxide, nitrogen and water. When the difference in jet pressure decreases or the elastic modulus of the rock increase, SC-CO2 jets boast more palpable advantages over nitrogen and water jets in rock breaking. This shows that SC-CO2 jets boast the potential of effectively breaking rock in deep formations.